2007
DOI: 10.1146/annurev.soc.33.040406.131710
|View full text |Cite
|
Sign up to set email alerts
|

Military Service in the Life Course

Abstract: We review research published in the past 15 years that explores the relationship between military service and the life course, focusing on criminal careers, marital status, lifelong health, and socioeconomic attainment. Throughout the review, we note the extent to which studies find that veterans experienced different outcomes in different historical periods, ranging from World War II to the more recent voluntary armed forces. The effects of military service depend on whether health, criminal, socioeconomic, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
188
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(197 citation statements)
references
References 102 publications
2
188
0
1
Order By: Relevance
“…Military service and life course theory are tied to global life choices explore and have similarities. Both combine factors such as age, gender, race, culture, crime, marital status, historical, lifelong health, and socioeconomic status resulting in ascribed and achieved attainment (MacLean and Elder, 2007). Military service is dependent on the era and the timing of service.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Military service and life course theory are tied to global life choices explore and have similarities. Both combine factors such as age, gender, race, culture, crime, marital status, historical, lifelong health, and socioeconomic status resulting in ascribed and achieved attainment (MacLean and Elder, 2007). Military service is dependent on the era and the timing of service.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The timeframe is even larger if we consider the health and wellbeing of the spouses and children of veterans as well (Levy and Sidel, 2009). More generally, learning about the potential long-term health consequences of previous military involvement can 1 See, for example, the range of findings and discussions in: Hearst et al, 1986;Breslin et al, 1988;Centers for Disease Control Vietnam Experience Study, 1988a, 1988bBoyle et al, 1989;Watanabe and Kang, 1996;DVA, 1999;Wilson and Horsley, 2003;Wilson et al, 2005aWilson et al, , 2005bWilson et al, , 2005cBoehmer et al, 2004;Boscarino, 2006;MacLean and Elder, 2007;McLaughlin et al, 2008;O'Toole et al, 1996O'Toole et al, , 1999O'Toole et al, , 2009and McBride et al, 2013. Some of the key health concerns for veterans that the literature has focused on are: poorer mental health, especially with respect to post-traumatic stress disorder (PTSD) and alcohol-related problems; greater risk of certain types of cancers resulting from chemical exposure in Vietnam (such as soft-tissue sarcoma); and a general heightened mortality risk, including from suicide and accidents.…”
Section: Introductionmentioning
confidence: 99%
“…For nearly three decades, a significant research tradition has evolved in the US which utilizes the life course perspective as a theoretical framework for understanding the impact of military participation, particularly service during periods of war, on subsequent life course outcomes, including educational attainment, health status, marital stability, socioeconomic mobility, and criminality (Lundquist 2004;MacLean and Elder 2007;MacLean 2010;Modell and Haggarty 1991;Sampson and Laub 1996;Settersten 2006;Wilmoth et al 2010;Xie 1992). The research has shown that the military is an important institution that can reshape one's life course trajectories and that the effects of military service are not always straightforward but tend to vary across pre-service individual characteristics, the timing of military service in the life course, duration of service, historical periods of service, conflicts of participation, and service experiences (e.g., draft status, branch of service, combat roles).…”
Section: Introductionmentioning
confidence: 99%